PENERAPAN METODE IMITASI DAN DRILL PADA PADUAN SUARA MANADO INDEPENDENT SCHOOL - Ferdinand Tonies Paputungan; Alrik Lapian (Institut Agama Kristen Negeri Manado, 2020)
Abstract Choir Class VII Students at the Manado Independent School is a newly formed choir group and most of the members cannot sing using good and correct vocal techniques due to their lack of knowledge of vocals in singing so it is necessary to apply methods to overcome these problems. The purpose of this study was to determine the application of the imitation and drill method at the Manado Independent School Choir. This study uses qualitative research methods, namely case studies. The analysis was obtained through a criteria assessment sheet consisting of six aspects of measurement consisting of posture, intonation, breathing, articulation, phasering, and expression. The results of the study showed two things, first, that the application of the imitation and drill method improved good vocal techniques, secondly, the imitation and drill method was the right method to be applied in the learning choir of Class VII Students of Manado Independent School.